2017
DOI: 10.3390/ijms18030569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silver Nanoparticles on Multiple Drug-Resistant Strains of Staphylococcus aureus and Pseudomonas aeruginosa from Mastitis-Infected Goats: An Alternative Approach for Antimicrobial Therapy

Abstract: Recently, silver nanoparticles (AgNPs) have been widely used in various applications as antimicrobial agents, anticancer, diagnostics, biomarkers, cell labels, and drug delivery systems for the treatment of various diseases. Microorganisms generally acquire resistance to antibiotics through the course of antibacterial therapy. Multi-drug resistance (MDR) has become a growing problem in the treatment of infectious diseases, and the widespread use of broad-spectrum antibiotics has resulted in the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
177
1
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(216 citation statements)
references
References 87 publications
20
177
1
6
Order By: Relevance
“…The bacteriostatic effect and adaptation of Pseudomonas DSM50026 to the tested annealed nanomaterials could be explained by the ability of this bacterial species to activate special transport pumps for an export of the nanoparticles or ions out of the cell. This fact is a possible mechanism of stress response as other researchers have reported .…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The bacteriostatic effect and adaptation of Pseudomonas DSM50026 to the tested annealed nanomaterials could be explained by the ability of this bacterial species to activate special transport pumps for an export of the nanoparticles or ions out of the cell. This fact is a possible mechanism of stress response as other researchers have reported .…”
Section: Resultssupporting
confidence: 66%
“…The doping of TiO 2 with Ag and Cu nanoparticles improved the photoresponse and photocurrent density of TiO 2 into the visible light region [21][22][23]. Other authors proved the several mechanisms of action of silver [17,18] and copper nanoparticles [16,20,21,24]. The combination of copper and silver nanoparticles leads to a stronger antibacterial effect at a lower concentration of eluted ions [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, a Trojan-horse like mechanism has been proposed, in which AgNPs first enter the cell and only then release silver ions (56). Previous studies showed that AgNPs promote the induction of reactive oxygen species (ROS) (57, 58) and enhance the expression of superoxide dismutase, catalase and peroxidase (58). These authors concluded that the main mechanism of antimicrobial action of AgNPs involves the disequilibrium of oxidation and antioxidation processes and the inability to eliminate ROS (58).…”
Section: Resultsmentioning
confidence: 99%
“…Because of this application, many methods and approaches concerning the synthesis of AgNPs, as well as silver‐based compounds containing ionic silver Ag (I) or metallic silver Ag (0) have been developed. Previously reported MIC values of AgNPs against P. aeruginosa and S. aureus were found to be 0.6–3 μg ml −1 and 0.8–7 μg ml −1 , respectively, using AgNPs in the size range between 5 and 30 nm . Because of higher surface area and more effective binding to the bacterial membrane, smaller AgNPs are considered to be more effective than larger particles.…”
Section: Resultsmentioning
confidence: 99%